Applicability of the effective-medium approximation to heterogeneous aerosol particles. (July 2016) - Mishchenko, Michael I.; Dlugach, Janna M.; Liu, Li
Abstract: The effective-medium approximation (EMA) is based on the assumption that a heterogeneous particle can have a homogeneous counterpart possessing similar scattering and absorption properties. We analyze the numerical accuracy of the EMA by comparing superposition T -matrix computations for spherical aerosol particles filled with numerous randomly distributed small inclusions and Lorenz–Mie computations based on the Maxwell-Garnett mixing rule. We verify numerically that the EMA can indeed be realized for inclusion size parameters smaller than a threshold value. The threshold size parameter depends on the refractive-index contrast between the host and inclusion materials and quite often does not exceed several tenths, especially in calculations of the scattering matrix and the absorption cross section. As the inclusion size parameter approaches the threshold value, the scattering-matrix errors of the EMA start to grow with increasing the host size parameter and/or the number of inclusions. We confirm, in particular, the existence of the effective-medium regime in the important case of dust aerosols with hematite or air-bubble inclusions, but then the large refractive-index contrast necessitates inclusion size parameters of the order of a few tenths. Irrespective of the highly restricted conditions of applicability of the EMA, our results provide further evidence that the effective-medium regime must be a direct corollary of the macroscopic Maxwell equations under specific assumptions. Highlights: Effective-medium regime can be realized for small inclusion size parameters. Threshold inclusion size parameter depends on the host and inclusion refractive indices. Effective-medium regime is confirmed for dust aerosols with hematite or air inclusions. Effective-medium regime must follow from the Maxwell equations.